Treatment of thigh abscess caused by retroperitoneal perforation of cecal cancer: A case report. (July 2022) - Iemura, Shunki; Mori, Shigeshi; Kamiya, Masato; Yamazaki, Kenji; Kobayashi, Takaya; Akagi, Masao; Togawa, Daisuke
Abstract: Introduction and importance: Iliopsoas and iliacus abscesses are caused by hematogenous and lymphatic infections and the spread of inflammation in neighboring organs. A small number of cases have been reported in which inflammation spread not only within the iliopsoas muscle but also to the thigh. Here we report a case of retroperitoneal infiltration and perforation of cecal cancer that caused extensive abscess formation from the iliacus muscle to the thigh. Case presentation: An 80-year-old man who had undergone chemotherapy for cecal cancer had abdominal pain and right thigh pain without any particular attraction. CT images showed extensive abscess formation from the iliacus muscle to the subcutaneous part of the thigh due to retroperitoneal infiltration and perforation of cecal cancer. Ileocecal resection, colostomy, and retroperitoneal abscess drainage were performed for perforation of cecal cancer and pelvic abscess. Although the thigh was initially drained by a small incision, the infection did not heal. Extensive debridement and drainage were required for all of the contaminated areas, and after all the infection was completely cured. Clinical discussion: The optimal treatment for an abscess that has spread from the inguinal region to the thigh is unclear. In this case, active debridement and drainage of the infected area were effective and should have been done early. Conclusion: We believed that debridement and drainage should have been performed from the time of the first surgery not only by the small incision drainage but also for all of the contaminated areas when the infection had been widespread. Highlights: ・The iliopsoas abscess may spread to the surrounding area in case its diagnosis is delayed. ・The optimal treatment for an abscess spreading from the inguinal region to the thigh is still controversial. ・Drainage by the small incision is not helpful when the infection has been spreading to the thigh, and all of the contaminated areas should also be exposed and active debridement and drainage are required.